2016
DOI: 10.1021/acs.nanolett.6b02454
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Interface in Oxide Homojunction: Understanding of Superior Properties in Black TiO2

Abstract: Black TiO2 nanoparticles with a crystalline core and amorphous-shell structure exhibit superior optoelectronic properties in comparison with pristine TiO2. The fundamental mechanisms underlying these enhancements, however, remain unclear, largely due to the inherent complexities and limitations of powder materials. Here, we fabricate TiO2 homojunction films consisting of an oxygen-deficient amorphous layer on top of a highly crystalline layer, to simulate the structural/functional configuration of black TiO2 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 36 publications
(66 reference statements)
0
42
0
Order By: Relevance
“…ii) The bandgap narrowing and the increased visible absorption will increase the efficiency of e–h pair generation η e–h . iii) The properly enhanced donor density will increase the efficiency of charge transport η trans . iv) Due to the low‐temperature treatment of HWA, the typical hydrogenation issues such as TiO 2 structure destruction and degradation of FTO will be avoided .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ii) The bandgap narrowing and the increased visible absorption will increase the efficiency of e–h pair generation η e–h . iii) The properly enhanced donor density will increase the efficiency of charge transport η trans . iv) Due to the low‐temperature treatment of HWA, the typical hydrogenation issues such as TiO 2 structure destruction and degradation of FTO will be avoided .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the black TiO 2 with disordered shell delivered superior properties to overcome the limitations of the large bandgap (rutile 3.0 eV; anatase 3.2 eV) and lower conductivity of pristine TiO 2 , and improve visible light absorption, charge separation, and electron transport in the photo‐electrochemical (PEC) process. Recently, Lü et al fabricated TiO 2 homojunction films with an oxygen‐deficient amorphous layer on top of a highly crystalline layer to simulate the similar structural and functional configuration of H–TiO 2 nanoparticles, and found that metallic conduction could be realized at the crystalline–amorphous homointerface via electronic interface reconstruction, which could explain the enhanced electron transport of black TiO 2 . Wang et al reported the visible‐light photocatalytic and PEC properties of aluminum‐reduced black TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…4 nm range of disordered shell. Recently Lü et al prepared TiO 2 homo-junction films consisting of an oxygen-deficient amorphous layer on top of a highly crystalline layer in order to simulate the crystalline core-disordered shell configuration of black TiO 2 nanoparticles [24]. They observed that metallic conduction was achieved at the crystalline − amorphous homo-interface via electronic interface reconstruction, which may be the main reason for the enhanced electron transport of black H-TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The high photoactivity was attributed to the Ti 3+ defects and disordered surface layer which resulted in a narrowed bandgap of 2.2 eV [93]. Recently, black amorphous TiO 2 film was achieved by pulsed laser deposition at 100°C for 10 min under vacuum condition using a commercial TiO 2 target and a KrF excimer laser at a repetition rate of 2 Hz with a laser fluence of 2 J·cm −2 [94]. This black amorphous TiO 2 film was deposited on a predeposited crystalline TiO 2 film to construct a bilayer structure similar to the crystalline/amorphous core/shell structure of black TiO 2 nanoparticles in order to create a simpler model to elucidate the working mechanism of black TiO 2 nanomaterials in many applications [94].…”
Section: Magnesium Reductionmentioning
confidence: 99%
“…This black amorphous TiO 2 film was deposited on a predeposited crystalline TiO 2 film to construct a bilayer structure similar to the crystalline/amorphous core/shell structure of black TiO 2 nanoparticles in order to create a simpler model to elucidate the working mechanism of black TiO 2 nanomaterials in many applications [94]. Metallic conduction was achieved at the crystalline/amorphous homointerface via electronic interface reconstruction [94]. This points to a research direction that may partly eluciate the high performance of black TiO 2 in many applications.…”
Section: Magnesium Reductionmentioning
confidence: 99%